Cytotoxicity of intraoral orthodontic elastics - Rogério Lacerda Santos; Matheus Melo Pithon; Márlio Vinícius Oliveira; Gabriella da Silva Mendes; Maria Teresa Villela Romanos; Antônio Carlos de Oliveira Ruellas (Universidade Estadual de Campinas, 2016)
Aim: The present study compared in vitro four types of latex intraoral elastics (5/16 = 7.9 mm, mean load) regarding their possible cytotoxic effects. Material and Methods: The sample was allocated to four groups of 24 elastics: Group A (American Orthodontics), Group M (Morelli), Group T (TP Orthodontics), and Group U (Uniden). Cytotoxicity assays were performed using cell culture medium containing epithelioid-type cells (Hep-2 line) derived from human laryngeal carcinoma. Two methods for evaluating the cytotoxicity, the agar overlay test and "dye-uptake" test, were employed at two different moments (0 and 24 h). Data were compared by analysis of variance (ANOVA) and Tukey's test (p<0.05). Results: The results showed statistically significant difference (p<0.05) between Groups T and M, T and U, A and M, and A and U, for dye-uptake test at 0 and 24 h. No cell lysis was found in Groups T and A for the agar overlay test, whereas 80% cell lysis was found in Groups M and U after 24 h according to the Stanford's response index (RI). Conclusion: Both TP Orthodontics and American Orthodontics elastics evoked less cell lysis than Morelli and Uniden elastics